Government Information Use by First-Year Undergraduate Students: A Citation Analysis - Sung, Sanga; Deeke, Alexander (Evidence Based Library and Information Practice, 2025)
Objective – The objective of the study was to investigate how first-year undergraduate students in a general education communication course engaged with government information sources in their academic research. The study examined the frequency, types, and access points of cited government information, as well as patterns in secondary citations and topic-based variation, to identify implications for library instruction, discovery systems, and collection strategies.Methods – For the study, the researchers analyzed citations from persuasive papers submitted by 136 students across 14 course sections. A total of 1,704 citations were reviewed, of which 124 were identified as government information sources. A classification scheme was developed to code citations by source type, government level, agency, and access point. Researchers also conducted a secondary citation analysis to identify where students referenced government-produced content through nongovernmental sources and categorized papers by topic to assess variation in government information use.Results – Government sources constituted 7.3% of all citations, with 45.3% of students citing at least one government source. Most cited materials came from U.S. federal agencies, particularly the Department of Health and Human Services and the U.S. Congress. Students predominantly accessed government sources through open Web sources, with minimal use of library databases and materials. The types of government sources most commonly cited were webpages, press releases, and reports. An additional 201 secondary citations referenced government information indirectly. Citation patterns varied by topic, with higher engagement in papers on government, immigration, and environmental issues.Conclusion – The findings suggest that even without explicit instruction or assignment requirements, undergraduate students demonstrated baseline awareness and independent use of government information sources. However, their reliance on open Web access and secondary references highlights gaps in discovery, evaluation, and access. Instructional support could enhance students’ ability to locate and critically engage with more complex and authoritative government documents. Beyond instruction, the findings inform strategies for enhancing discovery, improving visibility, and promoting balanced access to government information.